Lasers in Cardiovascular Interventions - Topaz, On (Springer London : Imprint: Springer, 2015)
This book provides the most authoritative, comprehensive and contemporary guide to technological progresses and clinical experiences of laser applications in cardiovascular medicine. Since the introduction of laser devices to the medical sciences, this technology has generated great interest. Specifically, the laser's unique physical properties and precise bio-tissue interactions render this versatile source of biologic energy an attractive tool for multiple therapeutic purposes in cardiovascular medicine. Over the course of the last two decades the utilization of laser technology has thus become an important component for the management of patients with complex cardiovascular diseases. Lasers in Cardiovascular Interventions is a valuable resource to this subject providing thorough yet practical information for cardiologists, vascular surgeons and interventional radiologists, as well as medical students, scientists, biomedical engineering students and graduates.